(untitled) (Scientific journal of the Fergana State University, 2024)
Since verbs are grammatically more complex than other word groups in all languages, viewpoints on it are controversial and interpretations vary. Such complexity, inherent in the verb, naturally gives rise to the variety of definitions given to this word class. This article discusses the phenomena of syncretism and polyfunctionality, their study in linguistics, the interpretations and functional-stylistic features of incomplete verbs in Uzbek and linking verbs in English. The syncretic nature and polyfunctional characteristics of incomplete verbs in Uzbek, primary auxiliaries and linking verbs in English are analyzed.